2018
DOI: 10.1016/j.schres.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Multisite generalizability of schizophrenia diagnosis classification based on functional brain connectivity

Abstract: Our objective was to assess the generalizability, across sites and cognitive contexts, of schizophrenia classification based on functional brain connectivity. We tested different training-test scenarios combining fMRI data from 191 schizophrenia patients and 191 matched healthy controls obtained at 6 scanning sites and under different task conditions. Diagnosis classification accuracy generalized well to a novel site and cognitive context provided data from multiple sites were used for classifier training. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…This bias might even be modality-specific, in that non-brain features might generalize better than brain imaging features (Bhagwat et al, 2018). Training predictive models on data from multiple sites has been shown to improve generalization (Abraham et al, 2017; Liem et al, 2017; Orban et al, 2018). Hence, future studies should use models trained and tested on data from multiple sites, which requires further suitable longitudinal and publicly available datasets (Varoquaux, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This bias might even be modality-specific, in that non-brain features might generalize better than brain imaging features (Bhagwat et al, 2018). Training predictive models on data from multiple sites has been shown to improve generalization (Abraham et al, 2017; Liem et al, 2017; Orban et al, 2018). Hence, future studies should use models trained and tested on data from multiple sites, which requires further suitable longitudinal and publicly available datasets (Varoquaux, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Bigger data sets are needed to avoid overfitting and to build a classifier with better generalizability. Second, only one modality of data (rsfMRI) was utilized, even though both functional and structural brain information may be important for high‐accuracy classification using machine learning (Mikolas et al, ; Orban et al, ; Ota et al, ). Third, we did not collect the smoking status of our participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It may thus be possible to extract multivariate biomarkers of brain diseases from such multisite harmonized data, as planned in the CCNA. Recent papers (Abraham et al, 2016;Orban et al, 2017) also showed that machine learning models trained on multisite rsfMRI data generalize better to subjects from new unseen sites, than models trained on single site data. Better approaches for site harmonization, either prospective like CDIP, or retrospective, for example (Yan et al, 2013) , may still increase the precision of rsfMRI biomarkers, and is an important area of future work.…”
Section: Precision Medicinementioning
confidence: 99%